Teori Konsumsi Islami Sebagai Pedoman Perilaku dan Penerapannya dalam Kehidupan - Rizki, Atika; Wahab, Abdul; Masse, Rahman Ambo (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2023)
Consumption is the most important form of activity for human life. This study aims to describe how consumption theory is in accordance with Islamic law, the definition of consumption according to Islam, how Islamic economics views consumption activities, the legal basis for consumption, Muslim consumer behavior, limits on consumption activities and the most effective method for carrying out the utilization hypothesis in daily life -day. This research is qualitative in nature. Secondary data for this research were collected from various scientific publications and books related to the topic under study. In addition, this study uses a literature study method for data techniques. The results of this study are that the application of Islamic consumption theory can be carried out in 4 stages. First, strive for a simple life and set aside wealth for things that are more important to achieve prosperity. Second, consumption activities must be based on halalan thoyyiban. Third, always be grateful, and fourth, always be generous towards others..